Fin whale song recordings by onshore seismometers open new horizons for cetacean coastal monitoring - Martin Möllhoff; Christopher J. Bean (Scientific Reports)
Abstract Fin whales, the second largest animal on Earth, produce one of the most intense vocalisations in the animal kingdom. Monitoring these songs using ocean-deployed hydrophones plays an important role in the study of fin whale distribution and social behaviour, though obtaining real-time data remains challenging. In this feasibility study we investigate if vocalising near-coastal fin whales can be widely detected and located with onshore seismometers. Inspecting data from pre-existing seismic installations we establish that fin whale song can be detected with onshore seismometers up to 5.5 km inland, across multiple marine environments, globally. Individual creatures can be located and tracked through the analysis of seismic wave properties. Furthermore, we show that citizen science seismometers, such as the affordable and widely deployed ‘Raspberry Shake’ devices, can reliably detect fin whale song. These instruments, often placed in coastal areas, provide real-time data, offering a cost-effective and accessible method for monitoring coastal fin whale activity. The revelation that human living spaces are ensonified by fin whale song offers the potential to enhance public engagement with the oceans and presents new opportunities for global monitoring. Fin whales are vulnerable to noise pollution, shipping strikes and entanglement in fishing gear. The use of terrestrial seismometers could improve early warning systems and contribute to richer datasets on near coastal whale vocalisations. This study demonstrates that, globally, seismic data holds significant untapped potential for near-coastal fin whale monitoring.